2011
DOI: 10.1002/lsm.21025
|View full text |Cite
|
Sign up to set email alerts
|

Single walled carbon nanohorns as photothermal cancer agents

Abstract: The significant increases in absorption, temperature elevation, and cell death with inclusion of SWNHs in laser therapy demonstrate the potential of their use as agents for enhancing photothermal tumor destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 40 publications
2
62
1
Order By: Relevance
“…However, the thermal conductivity of the solution is increased in higher concentrations, which dissipates more heat and thus makes the temperature drop slightly for higher concentrations. This maximum was not observed for our high laser power experiment (500 mW/cm 2 ) and in other studies that used higher laser power densities of 2 -4 W/ cm 2 and 40 W/cm 2 [24,26]. This might be because the heat dissipation effect of the thermal conductivity increasing occurred before the laser depletion, thus no maximum appeared.…”
Section: Figurecontrasting
confidence: 64%
See 2 more Smart Citations
“…However, the thermal conductivity of the solution is increased in higher concentrations, which dissipates more heat and thus makes the temperature drop slightly for higher concentrations. This maximum was not observed for our high laser power experiment (500 mW/cm 2 ) and in other studies that used higher laser power densities of 2 -4 W/ cm 2 and 40 W/cm 2 [24,26]. This might be because the heat dissipation effect of the thermal conductivity increasing occurred before the laser depletion, thus no maximum appeared.…”
Section: Figurecontrasting
confidence: 64%
“…They found that the solution temperature was increased for 1, 5, 10, 25 and 50 μg/ml, and saturated at 75 and 100 μg/ml. Whitney et al, [26] studied single-walled carbon nanohorns heated with a c.w. laser at wavelength 1064 nm and irradiance of 40 W/cm 2 for duration of 0-6 minutes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…They are novel nanostructure carbon materials generating much enthusiasm in biomedical applications, such as drug delivery, photo-hyperthermia (due to their intrinsic therapeutic effects), and magnetic resonance analysis, due to their several advantages over other carbon materials such as single-walled carbon nanotubes. [1][2][3][4][5][6][7][8][9][10][11][12] Besides their high purity, uniform size, and absence of metal catalysts, they have an extremely large specific surface area. 8 Furthermore, their surface area can be enlarged, holes can be opened, and oxygen functional groups can be introduced by oxidation at their …”
Section: Introductionmentioning
confidence: 99%
“…Nanocarbons, such as carbon nanotubes (CNTs) and carbon nanohorn (CNH), are considered useful in science and technology because of their remarkable physical and chemical properties, some of which might help overcome the limitations of traditional laser light technologies. In particular, nanocarbons have extraordinary photothermal energy conversion efficiency and high absorption cross-sections in a wavelength range capable of transmission within the diagnostic window (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Although gold nanoparticles also have such photothermal properties, nanocarbons can be more effectively heated at various wavelengths because of their strong absorbance over a wide range of the optical region (38).…”
mentioning
confidence: 99%